Review on Construction Procedures of Driving Cycles - Czégé, Levente; Vámosi, Attila; Kocsis, Imre (International Journal of Engineering and Management Sciences, 2020)
The goal of this paper is to give an overview of the literature of construction techniques of driving cycles. Our motivation for the overview is the future goal of constructing our own driving cycles for various types of vehicles and routes. This activity is part of a larger project focusing on determination of fuel and energy consumption by dynamic simulation of vehicles. Accordingly, the papers dealing with sample route determination, data collection and processing, driving cycle construction procedures, statistical evaluation of data are in our focus.